ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PERUSAHAAN INJECTION MOULDING - Ivan Bagus Achmal; Farizi Rachman; Dian Asa Utari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
CV. Anugrah Masrurah Teknik (AMT) is a company in the molding industry, especially Plastic Injection Molding, which produces interlock floors. The company often experiences a shortage of raw material inventory, causing uneconomical purchases and problems in the inventory and financial sectors. The main problem is raw material inventory planning that has not been maximized. This study uses the Economic Order Quantity (EOQ) method to identify the optimal purchase amount and prove whether this method can minimize the total inventory cost. The research objective is to determine the economic order quantity, order frequency, reorder point and safety stock. The results of the EOQ calculation show that the economic amount of raw material inventory is 1438 kg and results in cost savings of Rp. 17,157,133.